Analisis Faktor-Faktor yang Mempengaruhi Kinerja Keuangan pada Perusahaan Subsektor Industri Makanan Olahan yang Terdaftar di Bursa Efek Indonesia - Indri Adelia Br Sembiring; Aminuddin Aminuddin; Heny Triastuti Kurnia Ningsih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the effect of profitability and liquidity on financial performance. This type of research is descriptive quantitative, with a research sample of 12 processed food industry sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023, which was determined using a purposive sampling technique. The data source used in this study is secondary data, in the form of financial report data from processed food industry sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023 obtained from the Indonesia Stock Exchange website, namely www.idx.co.id and also the company's official website. The data analysis technique used is descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), hypothesis test (multiple linear analysis, partial t-test, Simultaneous F-test, and determinant coefficient test). The results of the study show partially, 1) Profitability has a positive and significant effect on the company's financial performance, 2) Liquidity has a negative and significant effect on the company's financial performance. While simultaneously 3) Profitability and liquidity have a positive and significant effect on the company's financial performance. With a coefficient determinant value of R Square of 0.865, it means that the independent variables (profitability and liquidity) have an influence on the dependent variable (financial performance) of 86.5%.